Pengaruh Kesadaran Membayar Pajak, Pengetahuan dan Pemahaman Peraturan Perpajakan, dan Kualitas Layanan terhadap Kemauan Membayar Pajak Wajib Orang Pribadi di Kota Tomohon - Lovihan, Siska (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2014)
Tax is a State financial resources, including individual taxpayers who became a mainstay of the government to obtain funds to finance the implementation of the country. For taxpayers who performing independent personal services no parties are forced to pay taxes. They have a tax ID because of their own free will. This phenomenon is deemed interesting to be associated with factors that encourage people to pay taxes, therefore this study will discuss the influence of the tax paying awareness, knowledge and understanding of tax laws, and the quality of service to the willingness paying taxes an individual taxpayer. Object of this study is the individual taxpayer who performing independent personal services registered in the Office of Counseling and Consultation Services Tax Tomohon the number of samples 77. T test used in hypothesis testing, to determine whether the independent variables significantly partially or not on the dependent variable and to determine the effect of independent variables on the dependent variable simultaneously used F test. Of the research that has been done, it is known that partial paying taxes awareness, and the quality of service significantly influence willingness paying taxes individual taxpayer in the city of Tomohon. While knowledge and understanding of tax laws do not significantly affect the willingness paying taxes an individual taxpayer in Tomohon. Taken together, paying taxes awareness, knowledge and understanding of tax laws, and the impact of service quality on willingness paying taxes individual taxpayer in Tomohon City.